2021
DOI: 10.1017/s1368980021004134
|View full text |Cite
|
Sign up to set email alerts
|

The protein gap—increasing protein intake in the diet of community-dwelling older adults: a simulation study

Abstract: Objective: Approximately 50% of Dutch community-dwelling older adults does not meet protein recommendations. This study assesses the effect of replacing low protein foods with protein-rich alternatives on protein intake of Dutch community-dwelling older adults. Design: The Dutch National Food Consumption Survey – Older Adults 2010-2012 was used for scenario modelling. Dietary intake was estimated for 727 adults aged 70+ based on two 24-h recalls. Commonly consumed products were replaced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…These complex processes occur within the context of omnivorous feeding, which includes the use of protein as a common/usual staple for energy generation. Our bodies need to maintain their total protein mass/pool as fully functional at any time, despite senescence [507,508] and even under the influence of MS [509,510]. This issue has, so far, been poorly studied for obvious methodological constrictions and even within the context of dietary needs, since many "recommendations" are no longer sustained by current knowledge.…”
Section: Cell-related Mechanisms: Bi Biochemical Inflammationmentioning
confidence: 99%
“…These complex processes occur within the context of omnivorous feeding, which includes the use of protein as a common/usual staple for energy generation. Our bodies need to maintain their total protein mass/pool as fully functional at any time, despite senescence [507,508] and even under the influence of MS [509,510]. This issue has, so far, been poorly studied for obvious methodological constrictions and even within the context of dietary needs, since many "recommendations" are no longer sustained by current knowledge.…”
Section: Cell-related Mechanisms: Bi Biochemical Inflammationmentioning
confidence: 99%
“…Different protein intake scenarios were calculated using the Dutch food consumption survey, in which regular food products were replaced by products (1) with a higher natural protein content, (2) enriched with protein, or (3) a combination of protein-rich and protein-enriched products. This theoretical approach showed that it is possible to increase protein intake (>1.0 g/kg bw/day) without a significant increase in the amount of food consumed [2]. We also studied different aspects of behaviour which influence the protein intake of older adults living at home.…”
mentioning
confidence: 99%
“…Another intervention to increase protein intake is to replace low-protein foods with alternative protein-enriched foods. In a simulation study by Verwijs et al [280] in com-munity-dwelling older adults, the percentage that reached the 1.0 gram of protein kg/ bw/day increased from 41.1% to 91.4% when products low in protein were substituted with protein-rich alternatives. However, these results were based on simulation data in the community and it remains unclear how effective this would be in practice.…”
Section: Discussionmentioning
confidence: 99%
“…One of the first steps is to optimize product choice by choosing energy/protein dense products [74]. A simulation study by Verwijs et al showed that optimization of food choice or the use of energy/ protein-enriched products could increase protein intake towards recommended levels [280], but research towards the effectiveness of increasing energy/protein density in the malnourished community-dwelling older adults is scarce [161]. When appetite is low and requirements are high, the use of oral nutritional support in the form of supplements is advised [74].…”
Section: Interventions For Late Phase Malnutrition In the Communitymentioning
confidence: 99%
See 1 more Smart Citation